Reducing torque ripple of induction motor control via direct torque control - Qasim Al Azze; Imad Abdul-Rida Hameed (Institute of Advanced Engineering and Science, 2023)
The induction motor is extremely well known and used as an alternating current (AC) machine. Therefore, torque and speed regulations are very essential for this type of machine. This paper presents direct torque control (DTC) based on induction motors (IM). The mathematical model of IM is reported, and the machine is modeled in a synchronous coordinate farm. Classic DTC is applied to IM with two bandwidths of hysteresis controller for electromagnetic torque and stator flux. The system is simulated and investigated via MATLAB/Simulink and the results carry out a high ripple on the torque. There are numerous of improving torque response, one of them is adding a new loop for speed with proportional, integral, and derivative (PID) controllers. IM model with PID based on DTC is simulated through MATLAB. A contrast performance of IM is presented between traditional DTC and DTC with PID. As result, the new DTC with PID carries out improvement in the speed response as well reduces the ripples of torque.